Sistem Manajemen Sekuriti PT. SK Keris Indonesia - Edy Susanto; Arya Bayu Sayeti; Niken Haq; Rewang Budi Prasetyo (Peneliti.net, 2023)
Security is an essential need for individuals, groups, and in the business world to create a security condition that is conducive to productivity advancement and advancing their welfare, therefore the community is required to participate in the administration of security. Security is a very important asset of the company, therefore security management is the responsibility of all parties, both owners and management, employees and the surrounding community. This research uses a qualitative approach, this approach is characterized by in-depth information search from several sources that are considered to have a significant role in the field of security. Data was collected through literature study. This study aims to determine the security management system at PT. SK Keris Indonesian, to find out the obstacles in implementing security at PT. SK Keris Indonesian and to find out the developments made in improving security at PT. SK Keris Indonesian. In implementing and administering the security system in the PT SK Keris Indonesian area. PT. SK Keris Indonesian is in fact still divided with an understanding of the duties and responsibilities of each. so that in handling the forms of disturbance that have occurred so far there is a lack of good relations and coordination between the police, security force officers, and the surrounding community